Incidencia de la instalación masiva de cocinas de inducción en el nivel de armónicos de la red secundaria de distribución en el alimentador centro de Latacunga de la estacion de distribución el Calvario de la Elepco S.A en el año 2016. Propuesta de un plan de acción para mantener un nivel permisible de contaminación por armónicos. - Vásconez Tovar, Julieta Nathalie (2017)
This research deals with the problem produced by the massive installation of induction cookers in low-voltage distribution networks for residential consumption on the level of harmonic disturbances presented by the energy supplied to the end user, which specifically corresponds to the Increase of the third harmonic component in percentages of approximately 9% of the value of the fundamental component of 60 Hz.